Effect of air bubbling on atrazine adsorption in water by powdered activated carbons : competitive adsorption of impurities - Wang, Rong (2013)
The effect of air bubbling on trace organic (atrazine) removal from water by powdered activated carbon (PAC) adsorption was investigated by injecting air bubbles at different flow rates into the solution as a mixing method in batch kinetic tests. The factors introduced by the use of air bubbling, such as pH increase, N2 and O2 competitive adsorption, mixing efficiency and contaminant release from PVC tubing were examined to identify their contributions to the change of atrazine adsorption efficiency caused by the air bubbling. The experiments revealed that the adsorption process could benefit from higher air bubbling rates. However, under some conditions, the uptake of atrazine was partially reversed after an initial rapid uptake. Several factors that could contribute to this undesirable effect have been examined. The evidence points to the detrimental effect of trace contaminants introduced by the plastic tubing delivering the air. All other factors examined had small to negligible impact. The leaked contaminants presented increasingly in the solution with operating time and competed with atrazine solutes for the active sites in the carbon particles and even displaced adsorbed atrazine over the 6-h kinetic test. As a result, atrazine adsorption efficiency was reduced. In contrast, when stainless steel tubing was used for air injection, no reversal phenomenon was observed in the bubbling batch kinetic adsorption tests. These observations may be important for hybrid adsorption-membrane processes which could use bubbling to provide mixing and fouling control. The common practice of using plastic piping for air delivery may need to be reconsidered especially for trace pollutants removal.